Building Analysis of the Lill Hajj Wall Umrah Building Based on Functionality of the Building for Umrah and Hajj Pilgrims - Lutfi, Muhamad; Chayati, Nurul; Prayudyanto, Muhammad Nanang; Insan, Muhammad Khaerul; Pratama, Septian Anggi (ASTONJADRO, 2023)
PT Lill Hajj Wall Umrah is targeted to get 5,226 consumers per year or equivalent to 436 people per month by 2030. The old office in the form of a shophouse with a building area of 119.75 m² for a capacity of 99 people is considered inadequate to serve 436 consumers per month, so PT Lill Hajj Wall Umrah needs a new office with a meeting room of at least 523.2 m². A new office will be planned based on SNI 2847-2019, SNI 1726-2019, SNI 1727-2020, and PBI 1983. The planning results are in the form of an analysis of the new office structure with building dimensions of 28.30 x 23.35m, four floors with a building area of 4,503 m². The material specifications of the building structure are concrete quality (fc’) 41.5 MPa, melted reinforcing steel quality (fy) 400 MPa (BJTS), and 280 MPa (BJTP). Basement floor column dimensions 0.6 x 0.6 m, first to fourth floor columns 0.5 x 0.6 m, rooftop columns 0.4 x 0.4 m, main beam dimensions 0.25 x 0.35 m, child beams 0.25x0.5 m, stair beams 0.25 x 0.35 m, roof deck beams 0.25 x 0.3 m and 0.3 x 0.4 m, concrete slab thickness 0.15 m. The results of structural modeling using the Etabs application showed that there was no over-strength (O/S) in the column and beam structure elements. The results of the design of the new office building Lill Hajj Wall Umrah in the form of a basement floor equipped with prayer room facilities covering an area of 14 m2, a generator room covering an area of 15.28 m2, a pump room covering an area of 15.28 m2, parking covering an area of 781.53 m2. The first floor is equipped with VIP room facilities covering an area of 33.33 m2, a prayer room covering an area of 25.87 m2, a toilet covering an area of 44.93 m2, and a boutique room covering an area of 55.22 m2, and a warehouse covering an area of 12.3 m2. The second floor is equipped with a meeting room covering an area of 47.9 m2, a manager’s room covering an area of 36.7 m2, a toilet covering an area of 30.9 m2, a prayer room covering an area of 16.08 m2, a boardroom covering an area of 80.59 m2 and a waiting room covering an area of 45 m2. The third and fourth floors are equipped with toilets covering an area of 25.75 m2, a prayer room covering an area of 23.95 m2, and a ballroom of 383.75 m2. The estimated budget for the construction of lill Hajj Wall Umrah’s new office is Rp 7.612.645.721.- and takes 406 working days for construction.